Exploiting Natural Variation of Secondary Metabolism Identifies a Gene Controlling the Glycosylation Diversity of Dihydroxybenzoic Acids in Arabidopsis thaliana. Issue 3 (29th August 2014) - Li, Xu; Svedin, Elisabeth; Mo, Huaping; Atwell, Susanna; Dilkes, Brian P; Chapple, Clint
Abstract: Plant secondary metabolism is an active research area because of the unique and important roles the specialized metabolites have in the interaction of plants with their biotic and abiotic environment, the diversity and complexity of the compounds and their importance to human medicine. Thousands of natural accessions of Arabidopsis thaliana characterized with increasing genomic precision are available, providing new opportunities to explore the biochemical and genetic mechanisms affecting variation in secondary metabolism within this model species. In this study, we focused on four aromatic metabolites that were differentially accumulated among 96 Arabidopsis natural accessions as revealed by leaf metabolic profiling. Using UV, mass spectrometry, and NMR data, we identified these four compounds as different dihydroxybenzoic acid (DHBA) glycosides, namely 2, 5-dihydroxybenzoic acid (gentisic acid) 5- O-β -D-glucoside, 2, 3-dihydroxybenzoic acid 3- O-β -D-glucoside, 2, 5-dihydroxybenzoic acid 5- O-β -D-xyloside, and 2, 3-dihydroxybenzoic acid 3- O-β -D-xyloside. Quantitative trait locus (QTL) mapping using recombinant inbred lines generated from C24 and Col-0 revealed a major-effect QTL controlling the relative proportion of xylosides vs. glucosides. Association mapping identified markers linked to a gene encoding a UDP glycosyltransferase gene. Analysis of Transfer DNA (T-DNA) knockout lines verified that this gene is required for DHBA xylosylation in planta and recombinant protein was able to xylosylate DHBA in vitro . This study demonstrates that exploiting natural variation of secondary metabolism is a powerful approach for gene function discovery.